Analysis Of Low-Code Adaptation In Industrial Era 4.0 Application Development In Indonesia - Rusdi, Methamazid; Paputungan, Irving Vitra (Jurnal Sains, Nalar, dan Aplikasi Teknologi Informasi, 2026)
Low‑code application platforms have emerged as an innovative solution for developing information systems that are fast, flexible, and easily adaptable to meet the demands of the Fourth Industrial Revolution (Industry 4.0). In Indonesia, this technology has attracted particular attention as it helps organizations address challenges such as limited skilled human resources and the need for substantial investment. With low‑code, applications can be developed with minimal coding—even by non‑technical users—through intuitive visual interfaces and drag‑and‑drop components. This accelerates development, reduces costs, and enhances efficiency, enabling organizations to adapt more quickly to changing business needs and remain competitive in the industry 4.0 era. This study analyzes the implementation of low‑code through a descriptive qualitative approach, using a case study at PT Partner Niaga Indonesia, Tangerang, and involving ten informants from diverse roles (CTO, application manager, QA engineer, and others). Thematic and SWOT analyses reveal that low‑code offers major strengths such as rapid development, cost efficiency, and productivity gains, while also presenting opportunities to support digital transformation in Indonesia. However, limitations in customization, security concerns, and integration with legacy systems remain significant challenges. The findings suggest that low‑code is an effective and efficient solution for organizations seeking to accelerate digitalization, with practical implications including the need for workforce training, strategies to mitigate technical debt, and careful vendor selection. The study is limited by the number of informants and its focus on a single company; future research should include quantitative assessments of cost–benefit impacts and comparative studies across different industrial sectors.